Sensitivity analysis of a conceptual model summing up different perspectives of the Barents sea and simulation of scenarios with qualitative methods - Valance, Arthur (HAL CCSD, 2021)
Qualitative modelling is an efficient technique for the analysis of complex socio-ecological systems. In the context of the integrated management plan of the Barents Sea, the qualitative modelling is a promising tool to develop socio-ecological conceptual models based on multiple stakeholders’ perspectives. In this study, we apply selected scenarios of changes in human activities and changes in the biomass of animal groups to assess the effects of cumulative impacts. The expected responses of the socio-ecological system components are presented using a model common to all stakeholders. The cumulative impacts described in this paper are mostly additive. Dedicated analyses reveal that the common model is quite robust to uncertain knowledge about connections and reflects rather well the perspectives of the various stakeholders. La modélisation qualitative est performante pour l’analyse de systèmes possédant de nombreux compartiments regroupés en secteurs variés et entretenant des interactions multiples et souvent complexes. Dans le cadre du plan de gestion intégrée de la mer de Barents, cette modélisation est un outil offrant des perspectives intéressantes pour la construction de modèles conceptuels socio-écologiques, inspirés des points de vue divers des parties prenantes Ce mémoire s’intéresse d’abord aux effets de scénarios combinés appliqués à un modèle commun résumant les points de vue divers des parties prenantes. La sensibilité de ce modèle est ensuite testée par rapport à l’ajout de connexions incertaines et une comparaison avec les modèles individuels est explorée. Nous montrons que le modèle commun est assez robuste aux incertitudes et qu’il résume relativement bien les diverses représentations de la mer de Barents.